Clinical and microbiological features of drowning-associated pneumonia: a retrospective multicentre cohort study. (January 2023) - Reizine, Florian; Delbove, Agathe; Tattevin, Pierre; Santos, Alexandre Dos; Bodenes, Laetitia; Bouju, Pierre; Fillâtre, Pierre; Frérou, Aurélien; Halley, Guillaume; Lesieur, Olivier; Courouble, Patricia; Berteau, Florian; et al.
Abstract: Objective: Pneumonia is the most frequent infectious complication in patients who have experienced drowning that requires intensive care unit (ICU) admission. We aimed to describe clinical, microbiological, and therapeutic data as well as predictors and impacts of such pneumonia on patients' outcomes. Methods: We conducted a retrospective, multicentre study (2013–2020) of 270 consecutive patients admitted for drowning to 14 ICUs in Western France. Their baseline characteristics and outcomes were compared according to the occurrence of drowning-associated pneumonia (DAP), defined as pneumonia diagnosed within 48 hours of ICU admission. A Cox regression model was used to compare survival on day 28, and logistic regression was used to identify risk factors for DAP. Microbiological characteristics and empirical antibacterial treatment were also analysed. Results: Among the 270 patients admitted to the ICU for drowning, 101 (37.4%) and 33 (12.2%) experienced pneumonia and microbiologically proven DAP, respectively. The occurrence of pneumonia was associated with higher severity scores at ICU admission (median Simplified Acute Physiology Score II, 34 [interquartile range IQR, 25–55] vs. 45 [IQR, 28–67]; p 0.006) and longer ICU length of stay (2 days [IQR, 1–3] vs. 4 days [IQR, 2–7]; p < 0.001). The 28-day mortality rate was higher among these patients (29/101 [28.7%] vs. 26/169 [15.4%]; p 0.013). Microbiologically proven DAP remained associated with higher 28-day mortality after adjustments for cardiac arrest and water salinity (adjusted hazard ratio, 1.86 [95% CI, 1.06–3.28]; p 0.03). A microbiological analysis of respiratory samples showed a high proportion of gram-negative bacilli (23/56; 41.1%), with a high prevalence of amoxicillin-clavulanate resistance (12/33; 36.4%). Conclusions: Pneumonia is a common complication in patients admitted in the ICU for drowning and is associated with increased mortality.